Public safety and cities: perspectives from the Chicago School - Guimarães, Claudio Alberto Gabriel; Branco, Thayara Castelo; Santoro, Antonio Eduardo (Revista de Direito da Cidade, 2021)
Abstract The aim of this work is, from the theoretical perspective developed by the Sociological School of Chicago, to investigate and rescue the studies conducted since the early twentieth century, which indicate the spatial configuration of cities as a factor inhibiting or enhancing criminal activity, depending on of their level of social and urban organization. Sequentially, based on studies by Brazilian researchers, it is intended to investigate the relevance of the interrelationship between social disorganization, urban disorganization and crime in the country, which leads to the following problematization: There is a relationship between socially and urbanistically disorganized city spaces and committing crimes? Finally, we will study the legal predictions, based on the Brazilian Constitution, about the development of public policies in such urban context, as a way to combat the violence pointed out by the research as socially and spatially sectorized. The research method used was strictly the bibliographic research and, consequently, the data used in the referred works and that pointed as hypothesis the plausibility in the connection between social disorganization, urban disorganization and crime suggesting, conclusively but not exhaustively, the need to implement inclusive public policies, especially within municipalities, focused on combating structural and, consequently, criminal violence.